2002
DOI: 10.1046/j.1365-2621.2002.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Extension of shelf‐life of whole‐wheat flour by gamma radiation

Abstract: The effect of low‐dose gamma irradiation (0.25–1.00 kGy) on pre‐packed whole‐wheat flour (atta) was assessed in terms of physico‐chemical properties, nutritional quality, chapati‐making quality and sensory attributes. Semi‐pilot scale storage studies on irradiated pre‐packed whole‐wheat flour revealed that there was no adverse effect of irradiation and storage up to 6 months of whole‐wheat flour treated at doses up to 1.00 kGy on total proteins, fat, carbohydrates, vitamin B1 and B2 content, colour index, sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 5 publications
5
16
0
9
Order By: Relevance
“…This phenomenon could indicate modifications in protein, but also could be attributed to changes in the starch as a result of endogenous amylolytic activity (Rehman and Shah, 1999). Indeed, an increase in low molecular weight carbohydrates has been reported in whole wheat flour during storage (Marathe et al, 2002). Low molecular weight carbohydrates in dough increase bread crust coloration due to the Maillard reaction (Pomeranz, 1988).…”
Section: Carbohydrate Degradation During Whole Wheat Flour Storagementioning
confidence: 99%
“…This phenomenon could indicate modifications in protein, but also could be attributed to changes in the starch as a result of endogenous amylolytic activity (Rehman and Shah, 1999). Indeed, an increase in low molecular weight carbohydrates has been reported in whole wheat flour during storage (Marathe et al, 2002). Low molecular weight carbohydrates in dough increase bread crust coloration due to the Maillard reaction (Pomeranz, 1988).…”
Section: Carbohydrate Degradation During Whole Wheat Flour Storagementioning
confidence: 99%
“…Arya et al (1977) preserved parothas by more than 6 months by reducing the concentration of sorbic acid from 0.48 to 0.25 % along with citric acid and giving an inpack heat treatment. The effect of low-dose gamma irradiation on prepacked whole wheat flour was assessed in terms of physico-chemical properties, nutritional quality, chapati making quality and sensory attributes by Marathe et al (2002). They reported that chapaties prepared using irradiated atta (0.25KGy) were preferred by the taste panelists even after 6 months of storage compared with control chapaties.…”
Section: Introductionmentioning
confidence: 99%
“…Tribolium castaneum is one of the most economically important stored product pests (Garcia et al 2005) distributed worldwide. It is a major pest that infests Rawa, a kind of semolina prepared from broken or crushed rice in India (Rao et al 1994;Marathe et al 2002;Pugazhvendan et al 2009) and despite utilizing an extremely large variety of foods, it is usually abundant in stored cereals and cereal products (Gupta et al 1999). Callosobruchus chinensis is the most serious pest of pulses in India and other tropical and subtropical countries (Upasani et al 2003).…”
Section: Introductionmentioning
confidence: 99%